Diatom Si deposition, spring warming duration, and spring mixing duration of sediment core Tiefer-See - Ulrike Kienel; Georgiy Kirillin; Brian Brademann; Birgit Plessen; Reinhard Lampe; Achim Brauer (PANGAEA, 2017)
Monitoring during three meteorologically different spring seasons in 2012, 2013, and 2014 revealed that temperature increase in spring, which influences spring lake mixing duration, markedly affected nutrient availability and diatom deposition in a sediment trap close to the bottom of deep Tiefer See, NE Germany. Deposition of Stephanodiscus taxa and small Cyclotella taxa was much higher after late ice out and a deep, short lake mixing period in spring 2013, compared to that after gradual warming and lengthy lake mixing periods in spring 2012 and 2014, when only brief or marginal ice cover occurred. Availability of dissolved Si and P was 33 and 20 % higher, respectively, in 2013 compared to 2014. The observed relation between high (low) diatom deposition and short (lengthy) mixing duration in spring was applied to varved sediments deposited between AD 1924 and 2008. Low detrital Si content in trapped material and a sediment core enabled use of μXRF-counts of Si as a proxy for diatom silica. The spring mixing duration for 1951-2008 was derived from FLake-model calculations. The spring warming duration related to lake mixing was approximated from air temperatures for 1924-2008 using the dates when daily mean air temperature exceeded 5 °C (start) and 10 °C (end). Diatom silica deposition showed a significant (p < 0.0001) inverse linear relationship with the modeled spring mixing duration (R**2 = 0.36) and the spring warming duration (R**2 = 0.28). In both cases, the relationship is strengthened when data from the period of low diatom production (1987-2005) is excluded (R**2 = 0.59 and R**2 = 0.35). Part of this low diatom production is related to external nutrient supply that favored growth of cyanobacteria at the expense of diatoms. This approach shows that diatom Si deposition was strongly influenced by the availability of light and nutrients, related to the duration of lake mixing and warming in spring, during most of the studied period. The remaining unexplained variability, however, indicates that additional factors influence Si deposition. Further tests in other deep, temperate lakes are necessary to verify if this relation is a common feature and consequently, if diatom Si can be used as a proxy for spring mixing duration in such lakes.
Supplement to: Kienel, U et al. (2016): Effects of spring warming and mixing duration on diatom deposition in deep Tiefer See, NE Germany. Journal of Paleolimnology, 57(1), 37-49, https://doi.org/10.1007/s10933-016-9925-z